CSR DAN KESEJAHTERAAN LOKAL : STUDI PADA RASIO UPAH PEGAWAI PEMULA DAN PEMBERDAYAAN MANAGER LOKAL PT PERTAMINA (PERSERO) 2020-2023 - Wahyu Mustika Rani; Alvyola Permata Yussanto; Puji Handayati; Makaryanawati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to analyze the contribution of PT Pertamina (Persero) Corporate Social Responsibility (CSR) to local economic welfare using Global Reporting Initiative (GRI) indicators EC5 (ratio of entry-level employee wages to Regional Minimum Wage) and EC6 (representation of local labor in managerial positions). The research uses a qualitative approach with a case study method, analyzing secondary data from PT Pertamina (Persero) 2020-2023 sustainability report. The sampling technique was carried out purposively on data relevant to the GRI indicators. The results showed that PT Pertamina (Persero) has not been transparent in reporting the ratio of entry-level wages to the UMR and the proportion of local managers in operational areas. This imbalance reflects the need to strengthen local workforce empowerment policies and pay equity as part of CSR strategies. The research conclusion confirms the importance of increasing the transparency of remuneration policies and optimizing the involvement of local communities in strategic positions to support the sustainability of company operation and socio-economic development